COMPLiCATiONS AFTER CYSTECTOMY AND THEiR TREATMENT - I. V. Semenyakin (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
We analyzed the results of treatment of 110 patients who had. cystectomy with, different types of urinary diversion. In the early postoperative period next complications occurred: prolonged intestinal paresis, dynamic ileus, thrombosis of the external iliac artery failure of intestinal anastomosis and the uretero-reservoir anastomosis, lymphocele formation, exacerbation of chronic pyelonephritis. In the late postoperative major complications were: urinary incontinence, stricture of the uretero-reservoir anastomosis, bladder stone formation. Conducted. operational and conservative methods of treatment allowed the arrest caused complications.